The spillover effects of foreign direct investment on labor productivity - Riesta Karentina (Economic Journal of Emerging Markets, 2019)
This study examines the effect of FDI spillovers, short-term and long-term effects of FDI spillovers on domestic firms’ productivity. It also explores the impact of FDI spillovers on domestic firms’ productivity in different groups of industries based on their factor intensity. Micro-level panel data covering about 20,000 medium and large manufacturing establishments in each year over the period 2010 and 2014 was employed. Findings/Originality: This study suggests that, within the same industry, horizontal spillovers are associated with domestic firms’ productivity: this relationship is negative in the short-term but positive in the long-term. It also demonstrates negative backward spillover effects on domestic firms’ productivity across industries. In addition, this study points out that FDI spillovers affect capital-intensive domestic firms’ productivity.